Problems of the Russian Market of Merger and Absorption Transactions - Yu, Ermolovskaya O. (Journal of Reviews on Global Economics, 2018)
Importance: Nowadays mergers and acquisitions, in addition to the organic growth, act as a tool for achieving competitiveness of the organization in the long run. While determining the strategic objectives of mergers and acquisitions, managers of the participants of transaction are driven by motives associated with obtaining synergetic effects, which require from the stakeholders concentration of resources, managers with sufficient experience and reasonable approaches to transactions at all stages. Thus, the complex of factors determines whether the transaction is successful and points out reasons for a failure. Objective: Develop the factors contributing to the failure in mergers and acquisitions at stages of implementation. Evaluate the necessity of measures, preventing failure of transaction and minimizing negative effects of it. Methods: Theoretical analysis, synthesis, systematization of scientific literature on the subject; structural analysis of mergers and acquisitions process, logical analysis of causes of unsuccessful transactions. Results: Determined the groups of factors weakening the ability to achieve success in mergers at stages of their implementation. Evaluated the necessity of measures, preventing failure of transaction. Conclusions and Relevance: It is concluded that mergers and acquisitions, despite their attractiveness for increasing business value even in times of deteriorating financial situation, carry many risks. In order to achieve desired effects, the parties involved in transaction must anticipate internal and external factors that can destroy the success of transaction on stages of preparation, closing the deal and in integration period, which determines the necessity of developing measures, minimizing negative effects of unsuccessful outcome of transactions.